Hepatoprotective and anti-inflammatory effects of new lectin purified from Morus nigra against lipopolysaccharideinduced oxidative stress in rats - AHLEM BAHI,; YOUCEF NECIB, (International Journal of Pharma and Bio Sciences, 2018)
The present study was undertaken to evaluate the protective effect of lectin purified from Morus nigra against lipopolysaccharide induced oxidative stress in experimental rats. Exposure of rats to lipopolysaccharide caused a significant increase in the lipid peroxidation level along with corresponding decrease in the reduced glutathione and various antioxidant enzymes in liver.and increase in serum: APL and transaminases activities. Supplementation of purified lectin of Morus nigra to lipopolysaccharide decrease in the serum the activities of AST, ALT and APL along with increase in liver GSH level and various antioxidant enzymes: glutathione peroxidase (GSH-Px), glutathione –S-transferase (GST) and catalase however the level of lipid peroxidation was increased in liver. Furthermore, no histological alterations were observed in the liver of lectin of Morus nigra. The results clearly demonstrate the protective role of new lectin purified from Morus nigra against LPS induced inflammatory liver in rats.